STRATEGI ANDROGINI CALON LEGISLATIF PADA PEMILU SERENTAK DI KECAMATAN KUTA UTARA - dani Praditya R, Kadek Yudha; Erawan, I Ketut Putra; Noak, Piers Andreas (Jurnal Nawala Politika, 2020)
ABSTRACT Androgyny carried out by legislative candidates in North Kuta in an effort to make a strategy to win the 2019 legislative elections. The author uses the theory of Androgyny from Sandra Lipitz Beam, this theory is useful to imply aid assistance that you want to ask and support, depending on situational suitability. With the Porposive method, the author obtained the results of the study consisting of: Legislative candidates both men and women were able to improve the Androgynic character when consulting themselves with their constituents, looking for potential legislators related to their masculinity by using direct spaciousness and looking for direct use of spaciousness and looking for direct Interesting constituents interesting legislative is able to combine with the value of the character of women (feminine) with regard to women's welfare. The interesting author using the Androgyny strategy will be a new step in winning the legislative candidates' future strategies. Keywords : Androgyny, Political Campaign, and Gender Strategy